2023
DOI: 10.1111/crj.13623
|View full text |Cite
|
Sign up to set email alerts
|

Aetiological distribution of pulmonary hypertension and the value of transthoracic echocardiography screening in the respiratory department: A retrospective analysis from China

Abstract: Methods The aetiological composition and clinical characteristics of patients with pulmonary hypertension (PH) hospitalised in the respiratory department were retrospectively analysed, as well as the correlation between transthoracic echocardiography (TTE) and right heart catheterization (RHC) for evaluating pulmonary artery systolic pressure (PASP) and mean pulmonary artery pressure (mPAP). Results Of 731 patients, 544 (74.42%) were diagnosed with PH by RHC. Pulmonary arterial hypertension (PAH) was the most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…A clinical study involving 731 patients in China found no significant difference between RHC and TTE in assessing sPAP in PH caused by hypoxia. Furthermore, Pearson correlation analysis between RHC and TTE demonstrated a moderate overall correlation (Hong et al, 2023;McGoon et al, 2004;Xu & Jing, 2009).…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…A clinical study involving 731 patients in China found no significant difference between RHC and TTE in assessing sPAP in PH caused by hypoxia. Furthermore, Pearson correlation analysis between RHC and TTE demonstrated a moderate overall correlation (Hong et al, 2023;McGoon et al, 2004;Xu & Jing, 2009).…”
Section: Introductionmentioning
confidence: 98%
“…Furthermore, Pearson correlation analysis between RHC and TTE demonstrated a moderate overall correlation (Hong et al, 2023;McGoon et al, 2004;Xu & Jing, 2009).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation